Identification of Muscle Fatique using Rapid Upper Limb Assessment (RULA) in Motorcycle Washing Activities - Juraida, Anita; Sunyoto, Annisa Maharani; Ratnasari, Ima; Nisfiani, Nurlaela (International Journal of Advanced Science and Technology, 2019)
Activities with awkward posture are susceptible to musculoskeletal disorders. Where the disorder attacks the muscles, tendons, ligaments, joints and cartilage) and the nervous system where injuries or disorders can affect almost all tissues including tendon sheaths. Motorcycle washing activities are very close to awkward postures, which will result in musculoskeletal nodding. The method of this research is to analyze the motor washing activity with RULA. The results obtained a score of 5, which means that it should be investigated for changes in posture or better work movements in motor wash activities. Keywords - Awkward Posture, Muscle Fatique, Musculoskeletal Disorders, RULA